Fatty acid profile of the mutton from Tsagaan-Uul breed (Mongolian Journal of Agricultural Sciences, 2023)
The objective of this research was to evaluate the chemical composition, muscle-to-bone ratio, fatty acid profile, and nutritional indexes (S/P, PUFA/SFA, n-6/n-3, AI, and TI) of the longissimus muscles (n=12) from pasture-raised Tsagaan-Uul breed sheep. The study focused on mutton from sheep aged 1.5, 2.5, and 3.5 years. The chemical composition of the meat varied with age. Total moisture content ranged from 56.6% to 62.2%, lipids from 19.1% to 24.9%, protein from 17.4% to 17.9%, and minerals from 0.7% to 0.8%. The muscle-to-bone ratio also increased with age, ranging from 5.2 to 6.3 kg. A total of 28 fatty acids were identified, with 50.56% being saturated fatty acids (SFA) and 49.35% unsaturated fatty acids (UFA). Among the 12 SFAs identified, palmitic acid (C16:0, 46.0%), stearic acid (C18:0, 28.4%), and butyric acid (C16:0, 11.5%) together accounted for 85.9% of the total SFA content. Seven different monounsaturated fatty acids (MUFA) were detected, with oleic acid dominating at 89.54%. Polyunsaturated fatty acids (PUFA) were dominated by linoleic acid (43.82%), α-linolenic acid (24.56%), and docosahexaenoic acid (16.64%), which made up 95.02% of the total PUFA content. The nutritional indexes, including the S/P ratio, n-6/n-3 ratio, AI, and TI, were found to be within recommended levels, except for the PUFA/SFA ratio. The observed variations in chemical composition and fatty acid profiles may be attributed to factors such as geographical location, diet, husbandry practices, and the timing of meat sampling.